THE IMPORTANCE OF DYNAMIC DRILLS IN SHAPING THE VOLLEYBALL PLAYERS' ENDURANCE - Bavatov Fayzulla Shamuratovich (Journal Park Publishing, 2023)
This article provides an overview of shaping the endurance of young volleyball players through active games.
Keywords: Physical qualities, volleyball, fitness, development, shaping, endurance.